Les Hommen: the language of reactionary masculinity. (23rd June 2018) - Russell, Eric
Abstract : This article examines the lexico-grammatical and lexico-pragmatic patterns of a social media corpus authored by les Hommen, a populist group of young French males who protested the enactment of same-sex marriage and parenting laws in late 2012 and early 2013. Through the close description of linguistic data and its interpolation via abstract discursive constructs of positioning and framing, it is argued that these praxes are not merely homophobic, but are also projections of reactive masculinity (i.e. a backlash against the perceived erosion of male hegemony triggered by the loi Taubira and its consequences). The article uses traditional and functional grammatical approaches to advance a view of the Hommen's cognitive context, manifest though linguistic performance, whereby the French male is projected as a simultaneous victim of and reactionary force against - in their view - an undemocratic administration, and sectarian LGBT and feminist activists.